Transgenerational effects of crude oil and heat shock on the mortality and oxygen consumption rate of Daphnia magna - Eklund, Joni (My University, 2022)
Baltic Sea is a compact area with heavy shipping activity, and since around 160 million metric tons of oil are transported annually, the risk of a major oil tanker spill is ever-present. Since climate change will raise sea temperatures forcing organisms to adapt or die, it is important to determine how the combined stress of oil exposure and rising temperature affects organisms. Daphnia magna, was chosen as test animal since with its parthenogenetic reproduction and short generation time, effects of exposures could easily be followed to the next generation, after the oil exposure is over. The hypothesis of this study is that the combined oil exposure and heat shock will lower the viability of D. magna and the effects are transferred to next generation. The first generation (F0) of the fleas was exposed to oil water soluble fraction (WSF) concentrations of 0 % (control), 10 % and 30 % for 24 hours, and the day after that to 30 °C heat shock for 24 hours (with 20 °C as control). Mortality, size and oxygen consumption rate of D. magna was measured after both exposures. First generation was allowed to reproduce, and the number of offspring (F1 generation) was measured. F1 generation oxygen consumption rate and size was measured, while continuing to monitor the F0 mortality. Both 30% WSF exposure and heat shock alone caused mortalities in F0 generation, but the mortality after heat shock was more than doubled in the population that received both treatments, when compared to population that experienced only WSF 30 % exposure (40 % vs. 13 %, respectively). Exposure to WSF 30 % and heat shock caused a significant decrease in oxygen consumption rate in F0 population (p<0.001). WSF and heat shock exposures had significant interacting effects on the oxygen consumption rates of the next generation. For the WSF 30 % + No-heat shock –F1 population, oxygen consumption rate was increased (p=<0.001) compared to WSF-control + No-heat shock, but no similar effect was seen in WSF 10 % + No-heat shock. In the heat-shock F1 population, WSF caused a decrease in oxygen consumption rate compared to WSF-control + heat shock (p=<0.001 in both WSF concentrations) along with a decrease in individual variation. Lowered oxygen consumption rate in F1 generations of parents that are exposed to WSF and heat shock is a response to stress, which together with the reduced variation could have negative effects on populations exposed to both oil and increased temperatures.
Keywords: Daphnia magna, crude oil, heat wave, transgenerational effects, ecotoxicology